A model for the development of service agreements in the Information and Communication Technology sector - Johnston, Robert (Rhodes University, Faculty of Commerce, Department of Information Systems, 2006)
SAs are documents that specify the business relationship between stakeholders to an outsourcing agreement. SAs specify this relationship in a legally binding manner that assists in managing expectations of the stakeholders about the service provision. According to Verma (1999), an SA is a precise statement of the expectations and obligations that exist in a business relationship between two organisation: the service provider and the client. In order for organizations to have successful outsourcing partnerships, they need well crafted methods of developing Service Agreements (SAs). Successful methods will produce a conclusive contract that will act as a working document that details the spirit of cooperation between the service provider and the service recipient. This research investigates the development of SAs in the Information and Communication Technology (ICT) sector, and proposes a model for their development. A number of models for SA development have been analysed. Models are analysed from leading researchers in the area, from software houses such as Microsoft and from international standards organisations such as the BS15000 which stipulates the ITIL framework. Eight development principles are identified and explored. An investigation into SAs and their development is conducted. A model is proposed that is composed of the development principles. The development of SAs was explored in an empirical study by means of a survey administered to industry practitioners and a series of interviews with managers in the ICT industry. The results of the study indicate varying levels of support for the development principles and limited relationship between the development principles and the success of the SA, as defined by the number of changes made to the SA after it is completed.
Keywords: Information technology; Communication -- Technological innovations; Service industries -- Management; Service -- Level agreements